KEBERHASILAN PERTUMBUHAN STEK JAMBU MADU (Syzygium equaeum) DENGAN PEMBERIAN ZAT PENGATUR TUMBUH KIMIAWI DAN ZAT PENGATUR TUMBUH ALAMI BAWANG MERAH (Allium cepa L) - Syariani BR Tambunan; Nico Syahputra Sebayang; Wazhi Aminoto Pratama (Universitas Islam Negeri Ar-Raniry, 2018)
The purpose of this research is to determine the growth of guava cuttings (Syzygium equaeum) by administering a chemical and natural growth regulator from onion extract (Allium cepa L). This study uses Factorial Randomized Block Design (RBD) consisting of 2 treatment factors and 3 replications. The first treatment is the utilization of chemical growth regulators, which consist of C0: no chemical growth regulator, C1: 20 ml chemical growth regulator / 1 liter of water) / cuttings; C2: 20 ml chemical growth regulator / 2 liters of water) / cuttings. The second treatment is the application of natural growth regulators onion extract, which consist of A0: no onion extract, A1: 20 ml onion extract /1 liter of water / cuttings, A2: 30 ml onion extract / 2 liters of water) / cuttings. The highest growth results of cuttings are in C0A1, C0A2 and C2A2, because of auxin and gibberellin hormone in C0A1 and C0A2 where the auxin lengthen the stem and roots, and the gibberellins support the leaf growth, and elongation of shoots and roots.